The Relationship of Leadership Style, Work Environment and Work Facilities on Employee Job Satisfaction in Omah Jenang MSMEs - Suprayitno, Hery; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to analyze the influence of leadership style, work environment and work facilities on employee job satisfaction at Omah Jenang MSMEs, located in Blitar Regency. The research method used is a qualitative approach with a case study design. Data was collected through in-depth interviews, direct observation, and analysis of related documents. The research results show that participative and transformational leadership styles contribute positively to employee motivation and job satisfaction. A harmonious work environment and a culture of mutual cooperation creates a comfortable working atmosphere, even though there are challenges such as hot temperatures in the production area. The available work facilities are sufficient to support the production process, but still require improvement, especially in the aspects of ventilation and personal protective equipment. This research concludes that the synergy between leadership style, work environment and work facilities has a significant influence on employee job satisfaction. These findings provide relevant insights for MSMEs to improve human resource management to achieve business sustainability.